An integrative approach to the facile functional classification of dorsal root ganglion neuronal subclasses - Giacobassi, Mario J. (Proc Natl Acad Sci U S A, 2020)
Somatosensory neurons have historically been classified by a variety of approaches, including structural, anatomical, and genetic markers; electrophysiological properties; pharmacological sensitivities; and more recently, transcriptional profile differentiation. These methodologies, used separately, have yielded inconsistent classification schemes. Here, we describe phenotypic differences in response to pharmacological agents as measured by changes in cytosolic calcium concentration for the rapid classification of neurons in vitro; further analysis with genetic markers, whole-cell recordings, and single-cell transcriptomics validated these findings in a functional context. Using this general approach, which we refer to as tripartite constellation analysis (TCA), we focused on large-diameter dorsal-root ganglion (L-DRG) neurons with myelinated axons. Divergent responses to the K-channel antagonist, κM-conopeptide RIIIJ (RIIIJ), reliably identified six discrete functional cell classes. In two neuronal subclasses (L1 and L2), block with RIIIJ led to an increase in [Ca](i). Simultaneous electrophysiology and calcium imaging showed that the RIIIJ-elicited increase in [Ca](i) corresponded to different patterns of action potentials (APs), a train of APs in L1 neurons, and sporadic firing in L2 neurons. Genetically labeled mice established that L1 neurons are proprioceptors. The single-cell transcriptomes of L1 and L2 neurons showed that L2 neurons are Aδ–low-threshold mechanoreceptors. RIIIJ effects were replicated by application of the K(v)1.1 selective antagonist, Dendrotoxin-K, in several L-DRG subclasses (L1, L2, L3, and L5), suggesting the presence of functional K(v)1.1/K(v)1.2 heteromeric channels. Using this approach on other neuronal subclasses should ultimately accelerate the comprehensive classification and characterization of individual somatosensory neuronal subclasses within a mixed population.